Vietnamese migrants in Russia : mobility in times of uncertainty - Hoang, Lan Anh, 1977- (Amsterdam : Amsterdam University Press, 2020)
Drawing on ethnographic research conducted at Moscow's wholesale markets from 2013 to 2016, this book provides original insights into how uncertainty shapes social practice, identity and belonging in the context of irregular migration from Vietnam to Russia. The uncertainties examined here are not just social, economic, and political, but also psychological and moral. The study speaks to various debates in migration and mobility studies - particularly those focused on brokerage networks, the political economy of sexuality, and social belonging - deepening our knowledge of how the core social values and cultural logics that underpin Vietnamese personhood are challenged and reconstituted by the ethos of the market economy. This book sheds important light on processes of mobility and social change in post-socialist societies that continue to grapple with yawning chasms between old and new ways of life, the local and the global, policy and practice, and obsolete governance techniques and rapidly changing socio-economic realities.
Frontmatter -- Table of Contents -- List of Maps, Photos and Tables -- Acknowledgements -- Tặng Một Người Bạn (For a Friend) -- I. Introduction -- II. Russia's post-Soviet migration regime -- III. Navigating Russia's shadow economy -- IV. Market ethos and the volatile radius of trust -- V. Love and sex in times of uncertainty -- VI. Transient existence and the quest for certainty -- Conclusion -- Appendix -- References -- Index
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed July 15, 2020).
eBooks on EBSCOhost
Keywords: Vietnamese -- Russia (Federation); Russia (Federation) -- Emigration and immigration; Vietnam -- Emigration and immigration; Vietnamiens -- Russie; 21st century history: from c. 2000-; Migration, immigration and emigration; The self, ego, identity, personality; HISTORY -- Modern -- 21st Century; Emigration and immigration; Vietnamese; Russia (Federation); Vietnam; Migration, mobility, uncertainty, Vietnam, Russia